High-Performance and Hysteresis-Free Perovskite Solar Cells Based on Rare-Earth-Doped SnO2 Mesoporous Scaffold - Qiyao Guo; Jihuai Wu; Yuqian Yang; Xuping Liu; Zhang Lan; Jianming Lin; Miaoliang Huang; Yuelin Wei; Jia Dong; Jinbiao Jia; Yunfang Huang (Research, 2019)
Tin oxide (SnO2), as electron transport material to substitute titanium oxide (TiO2) in perovskite solar cells (PSCs), has aroused wide interests. However, the performance of the PSCs based on SnO2 is still hard to compete with the TiO2-based devices. Herein, a novel strategy is designed to enhance the photovoltaic performance and long-term stability of PSCs by integrating rare-earth ions Ln3+ (Sc3+, Y3+, La3+) with SnO2 nanospheres as mesoporous scaffold. The doping of Ln promotes the formation of dense and large-sized perovskite crystals, which facilitate interfacial contact of electron transport layer/perovskite layer and improve charge transport dynamics. Ln dopant optimizes the energy level of perovskite layer, reduces the charge transport resistance, and mitigates the trap state density. As a result, the optimized mesoporous PSC achieves a champion power conversion efficiency (PCE) of 20.63% without hysteresis, while the undoped PSC obtains an efficiency of 19.01%. The investigation demonstrates that the rare-earth doping is low-cost and effective method to improve the photovoltaic performance of SnO2-based PSCs.